Chitosan nanoparticles loaded with 2,5-dihydroxybenzoic acid and protocatechuic acid: Properties and digestion - Madureira, Ana Raquel (2017)
Research efforts on the production of chitosan nanoparticles (NP) as delivery systems of bioactive compounds such as polyphenols have been made along the last decade. Nevertheless, the effect of the phenolic compound structure in the production of these NP was never evaluated so far. Low and high molecular weights chitosan (LMWC and HMWC) NP loaded with the phenolic acids, protocatechuic (PA) and 2,5-dihydroxybenzoic acids (2,5-DHBA) were produced by ionic gelation. Antioxidant activities were determined by ORAC assay. Physical and thermal properties were evaluated by dynamic light scattering (DLS) and differential scanning calorimetry (DSC), respectively. Stability and release of phenolic acids during simulation of gastrointestinal tract (GIT) conditions were also assessed. Nanoparticles sizes ranged from 300 to 600 nm and maintained stable during storage at 4 C during 30 d. Antioxidant activities of the phenolic acids decreased when loaded in the NP. High molecular weight chitosan NP adsorbed higher energy and melted at lower temperatures than LMWC NP. Nanoparticles produced with HMWC released higher phenolic acids % at GIT simulated conditions and with slight increases in their sizes. The most proper systems for delivery of PA and 2,5-DHBA were found to be LMWC and HMWC NP, respectively. These NP could be used to as functional food ingredients or as models for production of phenolic acids-rich extracts NP for future incorporation in food matrices.